Implikasi Pandemi Covid-19 Terhadap Kreativitas Desain Pembelajaran Guru PAI di MTsN 8 Ngajuk - Mukhamat Saini (STAI Ihyaul Ulum Gresik, 2022)
The teacher's ability to deliver lessons is an important factor in determining the speed at which a learning cycle can be achieved. An educator should have the option to combine material carefully and focus on delivery strategies. The success of the teacher in delivering the material is very dependent on the smooth communication with students. In line with that, it is important to have learning media that work with the correspondence between educators and students. The objectives of this research are, first, to find out the forms of distance learning designs during the Covid-19 era by PAI teachers at MTsN 8 Nganjuk. Second, to describe the supporting factors of PAI teachers in presenting distance learning at MTsN 8 Nganjuk. Third, describe the inhibiting factors for PAI teachers in presenting distance learning at MTsN 8 Nganjuk. This research is included in qualitative research. In this study, PAI teachers became the object of research. The approach used in this research is a qualitative approach. This means that the data collected is not in the form of numbers, but the data comes from interview scripts, field notes, and other official documents. The results show that: First, the form of assignment to students is to use several applications used by teachers in carrying out online learning such as Whatsapp, Google Form, Google Meet, and Youtube. Second, the supporting factor of this online learning process, namely, the school facilitates wifi for teachers to support the online learning process while the teacher is at school. The wifi facility provided by the school is used to make learning videos and provide these learning videos to students. Third, the inhibiting factor in implementing online learning at MTsN 8 Nganjuk, namely, the lack of effectiveness and time efficiency due to parents who are busy working. As for the other inhibiting factors, namely, constrained in the signal and internet quota. Another inhibiting factor in implementing online learning is the lack of student enthusiasm.